Where Do We Look Now? The Future of Research in Indigenous Australian Education - Harrison, Neil (The Australian Journal of Indigenous Education, 2007)
Abstract Research in Indigenous Australian education is at a dead-end. Researchers are still heading out into the field to look for new knowledge to answer old questions. The same epistemology dominates how we look, and where, while the methodology provides the researcher with a forced choice, one where either the student or the teacher is blamed for the lack of outcomes in Indigenous education. Where do we look now, and can we find something that has not been found before? The unequal historical relation that persists across Australia suggests that the process of research itself could be given as much attention as the search for quantifiable outcomes. The paper proposes that this process focus on the production of relations between schools and communities as well as on the search for knowledge.